“Factors influencing the demand for halal foods purchase intention in kelantan” - Audra Suzzy Lee Anak Samuel Law; Nurulizzati Atan; Nur Taqiah Razmi; Siti Aisyah P Ramli (2023)
This study investigates the factors influencing the demand for Halal foods purchase intention in Kelantan. This study examines how consumers choose halal food based on their intention before purchasing. This study adopts the quantitative method using survey approach through the use of questionnaires (via google form) to collect data from respondents. A total of 210 respondents have been sampled. Findings reveal that the mean value for Halal certification is 4.7229, food quality is 4.6429 and religiosity is 4.7124. The result of the reliability test shows Cronbach's Alpha value for independent variables is 0.909, 0.839, 0.900, and for dependent variables is 0.905. Lastly, Pearson’s correlation results show that halal certification, food quality, and religiosity have significant relationships with halal foods purchase intention in Kelantan.